The Amygdala A Discrete Multitasking Manager - Ferry, Barbara (IntechOpen, 2012)
Among the components of the limbic system, the amygdala is a fascinating structure that is involved in the processes of liking and disliking and in the ways our emotions drive our actions and affect the strength of our memories. Combined with new conceptual breakthroughs, the very latest data obtained by leading world experts in amygdala function that are reviewed in this book have helped to understand how the amygdala contribute to these processes and also to a variety of neurological and neuropsychiatric pathologies. Of course, due to the rate of research advancement, all the chapters presented here correspond to precise questions addressed by experts using highly specific techniques. Therefore, each chapter should be viewed as pieces of a puzzle that represent all the different research areas that have to be taken into consideration in discussing the role of the amygdala in emotion and memory. Although the primary goal of this book is to inform experts and newcomers of some of the latest data in the field of brain structures involved in mechanisms underlying emotional learning and memory, we hope it will also help to stimulate discussion on the functional role of the amygdala and connected brain structures in these mechanisms.